Guidelines to perform practical works on discipline "Social and labor relations in the organization of accounting activities" - Yurieva, Iryna (National Technical University "Kharkiv Polytechnic Institute", 2024)
Ukraine's integration into the world economic space requires introducing a fundamentally new organizational and economic mechanism for regulating labor and payment. It should be based on modern, progressive international financial reporting standards, methodology, and accounting organization. It determines the relevance of research and evaluation of accounting support in the labor relations system and defines the main directions of their improvement. The need to develop scientifically sound provisions in terms of accounting support and regulation of business operations of the enterprise in the system of labor relations is due, firstly, to the improvement of legal mechanisms for their regulation and the improvement of the legal protection of citizens who are subjects of the organization of remuneration. Secondly, to introduce new principles of wage policy formation, reform in the field of wages, the emergence of objects in terms of employee benefits, which became widespread as a result of the integrated application of P (S) BO 26 and the reform of the pension system, information on which for the needs of users is formed in the accounting system enriched with new content. The discipline "Social and labor relations in the organization of accounting activities" is one of the subjects studied due to changes in the economic development of Ukraine. Important in preparing modern specialists is the formation of knowledge and management skills in non-standard crises and emergencies. The purpose of studying the discipline is to form in future specialists the knowledge and skills of social management in social and labor relations in the organization of accounting activities. Formation of students' conceptual system of theoretical and practical issues based on social and labor relations in the organization of accounting activities and relevant professional competencies.
Keywords: guidelines; economic activity; finance; labor relations; ethics; consumer budget; minimum wage